Take the honey and run - Marts, Jennie (Marts, Jennie. Bee keeping mystery, 2023)
"As a successful mystery author, Bailey Briggs writes about murder, but nothing prepares her for actually discovering the dead body of the founder of her hometown of Humble Hills, Colorado. Bailey grew up at Honeybuzz Mountain Ranch and was raised by her beekeeping grandmother, Blossom Briggs, aka Granny Bee, and her two eccentric sisters, Aster and Marigold--which is why she drops everything to come home and help Granny Bee after a bad fall. A broken foot doesn't stop her grandmother from ruling The Hive, her granny's book club, or continuing to prepare and package her bee-inspired products. But when Bailey's grandmother's infamous "Honey I'm Home" hot spiced honey turns out to "bee" the murder weapon and her granny is now the prime suspect, Bailey has no choice but to use her fictional detective skills to help solve the murder and "smoke out" the real culprit. With the help of Bailey's witty bestie, a pair of meddling aunts, the feisty members of The Hive, and her computer-savvy daughter, this amateur sleuth is determined to solve the case. A malicious attack and an ominous threat reveal that someone wants Bailey to butt out of the investigation, but there's no way she's backing down. She must use her skills to uncover the truth and catch the clever culprit before her grandmother ends up bee-hind bars"--